Late-onset first epileptic seizure and cerebral small vessel disease: role of juxtacortical white matter lesions - Adrian Nasca; Adrian Nasca; Leo Sokolovič; Leo Sokolovič; Oliver Koprda; Patrick Haage; Patrick Haage; Thorsten Schmidt; Juraj Kukolja; Juraj Kukolja (Frontiers in Neurology)
ObjectiveThe cause of late-onset first epileptic seizures (LOFES) in older age is often not readily evident. In absence of probable causes, it has been suggested that cerebral small vessel disease (CSVD), which is common with increasing age, may be crucial. We aimed to further investigate the impact of white matter lesion (WML) burden and distribution pattern on LOFES.MethodsWe retrospectively compared structural MRI of LOFES patients (n = 39) aged 60 years or older to controls with a transient ischemic attack (TIA, n = 38) and to patient controls (n = 35). WML segmentation was performed on FLAIR images using the SPM based automated lesion prediction algorithm of the LST toolbox and careful manual adjustment. Further, a dichotomization of WML was achieved by use of the BIANCA masking function. A voxel-based morphometry (VBM) analysis was additionally performed on T1 weighted sequences using the automated SPM12 based CAT12 software.ResultsComparing intrapersonal volume ratios adjusted for the effects of gender and age, we found that the WML distribution was shifted to the juxtacortical compartment in LOFES patients. Among several influencing variables a path analysis could additionally show that this juxtacortical weighting of WML was a significant predictor for LOFES (β = 0.509, p < 0.001). With regard to total WML volume, LOFES and TIA patients did not differ significantly. Compared to TIA group, LOFES patients gray matter volume was regionally decreased in the right pre- and postcentral gyrus.SignificanceBy using algorithm-based automated lesion segmentation software tools and VBM analysis we could highlight that a juxtacortical weighting of WML distribution and regionally decreased gray matter volume distinguished LOFES from TIA and PC groups in our sample.